2021
DOI: 10.1101/2021.08.02.454728
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gene-dependent yeast cell death pathway requires AP-3 vesicle trafficking leading to vacuole membrane permeabilization

Abstract: Unicellular eukaryotes are suggested to undergo self-inflicted destruction. However, molecular details are sparse by comparison to the mechanisms of cell death known for human cells and animal models. Here we report a molecular pathway in Saccharomyces cerevisiae leading to vacuole/lysosome membrane permeabilization and cell death. Following exposure to heat-ramp conditions, a model of environmental stress, we observed that yeast cell death occurs over several hours, suggesting an ongoing molecular dying proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 104 publications
(145 reference statements)
1
1
0
Order By: Relevance
“…A recent study identified that the AP-3 adaptor complex is a death-promoting factor during heat-induced cell death and is also involved in vacuole permeabilization. A recent study uncovered that disruption of the AP-3 adaptor complex, which promotes stress-induced cell death by transporting and installing proteins on the vacuolar membrane, confers resistance to AA and hydrogen peroxide [52]. Since Zrt3 is a candidate cargo protein for the AP-3 adaptor complex, those results are consistent with the data obtained in this study linking absence of Zrt3 from the vacuole with a cell death resistance phenotype.…”
Section: Discussionsupporting
confidence: 91%
“…A recent study identified that the AP-3 adaptor complex is a death-promoting factor during heat-induced cell death and is also involved in vacuole permeabilization. A recent study uncovered that disruption of the AP-3 adaptor complex, which promotes stress-induced cell death by transporting and installing proteins on the vacuolar membrane, confers resistance to AA and hydrogen peroxide [52]. Since Zrt3 is a candidate cargo protein for the AP-3 adaptor complex, those results are consistent with the data obtained in this study linking absence of Zrt3 from the vacuole with a cell death resistance phenotype.…”
Section: Discussionsupporting
confidence: 91%
“…Heat tolerance. To determine if resistance to cell death may be related to virulence in these strains, we compared the mouse passaged isolates to the patient strain in a cell death assay that has been previously demonstrated to induce gene-dependent cell death in S. cerevisiae, and more recently in C. neoformans (39,40). To assess cell death susceptibility, a transient sublethal heat-ramp (not heat shock) was applied to all isolates and survival was determined by CFUs when plated at 30°C.…”
Section: Resultsmentioning
confidence: 99%